Proposed Marketing Strategy for Qwords.com Web Hosting: Usulan Strategi Marketing Untuk Qwords.com Web Hosting (The Indonesian Journal of Business Administration, 2012)
This final project explores the problems faced by Qwords.com through some analysis. External environment that affect the opportunity and threat that experienced by the company is divided into two aspects, macro and micro. External environment macro analysis that has influence indirectly to the company's activities is analyzed using a PEST modeling. The external environment micro analysis is analyzed using Porter's Five Forces Model. The Segmentation, Targeting, and Positioning of Qwords' web hosting will be analyzed, then analysis of marketing strategies (marketing mix) using 7P's model and SWOT analysis. It also examined the knowledge and consumer behavior to the web hosting product with using questionnaires. All analyzes are conducted to formulate the root cause of the problem that being faced by the company.From the results of the business issues exploration, we can get the cause of the problem are the high level of competition between web hosting providers, so there is a price war among web hosting providers and the company doesn't have the proper positioning formula for its web hosting product and segmentation for the customer that still limited to analyze by the company. Lack of marketing effort and market education about the web hosting products, so there is lack of consumer awareness of these products and there are perceptions from customer about the expensive of hosting product and lack of consistent and sustainable effort to promotional activity, so that making the company difficult to gain large market share.To overcome this, the company doing the mapping of potential markets that will be targeted, along with plan for positioning formula, in order to promotional activities that conducted by the company can run effectively and efficiently. The company also makes a partnership with college institutions and blogger communities, the purpose is to conduct education to consumer in the market towards web hosting products, and it can also be used by companies to increase sales volume. A variety of internet marketing activities can be performed as an alternative marketing strategy. It is considered because the high level of Internet usage in Indonesia at this time. Internet marketing strategy also does not require a lot of cost for implementation, so that companies can save the costs that being used for marketing activities. Keywords: Marketing Strategy, Web Hosting, Marketing Mix, Potential Market